Lost in the storm - Holly Webb; Sophy Williams (London, Stripes, 2007)
Ella loves her kitten, Fluff, and worries about her going missing again. But Fluff ejoys the freedom of being outside, especially when it starts snowing and she has the pretty snowflakes to play with and lots of wintry gardens to explore. But suddenly a blizzard sets in and Fluff can't find her way home. Will Ella ever be reunited with her kitten?
Keywords: Storybook